Service Quality in Issuing Certificates of Poverty in Watuliandu Sub-District Kolaka - Wafhiqa Annisa; Achmad Lamo Said; Nimrah Rahmayanti Yusuf (Teras Kampus, 2025)
This study aims to analyze the quality of service in the issuance of the Poor Certificate (Surat Keterangan Tidak Mampu/SKTM) at Watuliandu Village, Kolaka District, Kolaka Regency. SKTM is a crucial document that enables underprivileged citizens to access social assistance and government welfare programs. Using a qualitative research approach, data was collected through observations, interviews, literature reviews, and document analysis. The findings indicate that the overall quality of SKTM services is generally good and efficient, as assessed through five key service quality indicators: tangibles, reliability, responsiveness, assurance, and empathy. However, several issues still hinder optimal service delivery. These include delays caused by the unavailability of the Village Head for document signing, inconsistent responsiveness among service staff, and varying degrees of empathy shown toward applicants. Based on these findings, the study recommends prompt coordination for document authorization, improvements in queue management systems, and enhanced staff training to increase professionalism and responsiveness, ultimately ensuring better service delivery for the community in need.